2005
DOI: 10.1021/bi048005m
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Mechanism and Substrate Specificity of RhlI, an Acylhomoserine Lactone Synthase from Pseudomonas aeruginosa

Abstract: The enzyme RhlI catalyzes the formation of N-butyrylhomoserine lactone from S-adenosylmethionine and N-butyrylacyl carrier protein. N-Butyrylhomoserine lactone serves as a quorum-sensing signal molecule in Pseudomonas aeruginosa, and is implicated in the regulation of many processes involved in bacterial virulence and infectivity. The P. aeruginosa genome contains three genes encoding acyl carrier proteins. We have cloned all three genes, expressed the acyl carrier proteins, and characterized each as a substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(89 citation statements)
references
References 16 publications
3
85
1
Order By: Relevance
“…It appears, however, that molecular oxygen is not directly involved in the synthesis of HSL-based autoinducers. Synthesis of 3-oxo-C 12 -HSL and C 4 -HSL by their cognate autoinducer synthase (i.e., LasI and RhlI) requires S-adenosylmethionine (SAM) and 3-oxo-C 12 -acyl carrier protein or the N-butyryl acyl carrier protein, respectively (18,38). Our qRT-PCR analysis results shown in Fig.…”
Section: Discussionmentioning
confidence: 81%
“…It appears, however, that molecular oxygen is not directly involved in the synthesis of HSL-based autoinducers. Synthesis of 3-oxo-C 12 -HSL and C 4 -HSL by their cognate autoinducer synthase (i.e., LasI and RhlI) requires S-adenosylmethionine (SAM) and 3-oxo-C 12 -acyl carrier protein or the N-butyryl acyl carrier protein, respectively (18,38). Our qRT-PCR analysis results shown in Fig.…”
Section: Discussionmentioning
confidence: 81%
“…A previous kinetic analysis of an acyl-HSL synthase, RhlI, suggested that the ionizing residue plays a part in the acylation reaction that leads to deprotonation of the α-amino group of SAM and subsequent nucleophilic attacks on the thioester bond of acyl-ACP (21). After acylation, lactonization appears to proceed via a direct attack of the carboxylate oxygen on the methylene carbon adjacent to the sulfonium ion within an N-acyl-SAM intermediate (21).…”
Section: Discussionmentioning
confidence: 99%
“…After acylation, lactonization appears to proceed via a direct attack of the carboxylate oxygen on the methylene carbon adjacent to the sulfonium ion within an N-acyl-SAM intermediate (21). In particular, various experiments consistently indicated that this lactonization step does not require a general acid-base catalysis (21).…”
Section: Discussionmentioning
confidence: 99%
“…5), arginines 19 and 41 interact with the phosphate, and the guanidinium group of Arg 41 stacks onto the adenine rings to fully enclose this end of the cofactor. Also, the backbone amides of Arg 41 , Asp 42 , and Leu 66 as well as the hydroxyl of Ser 18 mediate hydrogen bonding interactions. Finally, it may be significant that only one active site in the asymmetric unit has a bound cofactor because both active site clefts are accessible in the crystal packing arrangement.…”
Section: Resultsmentioning
confidence: 99%